Developing an ionospheric map for South Africa - Okoh, Daniel Izuikeninachi (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2009)
This thesis describes the development of an ionospheric map for the South African region using the current available resources. The International Reference Ionosphere (IRI) model, the South African Bottomside Ionospheric Model (SABIM), and measurements from ionosondes in the South African Ionosonde Network, were incorporated into the map. An accurate ionospheric map depicting the foF2 and hmF2 parameters as well as electron density profiles at any location within South Africa is a useful tool for, amongst others, High Frequency (HF) communicators and space weather centers. A major product of the work is software, written in MATLAB, which produces spatial and temporal representations of the South African ionosphere. The map was validated and demonstrated for practical application, since a significant aim of the project was to make the map as applicable as possible. It is hoped that the map will find immense application in HF radio communication industries, research industries, aviation industries, and other industries that make use of Earth-Space systems. A potential user of the map is GrinTek Ewation (GEW) who is currently evaluating it for their purposes
Keywords: Ionosphere -- South Africa; Shortwave radio; Ionospheric electron density -- South Africa